3m+1-1m=-7+3m-1+1

Simple and best practice solution for 3m+1-1m=-7+3m-1+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m+1-1m=-7+3m-1+1 equation:


Simplifying
3m + 1 + -1m = -7 + 3m + -1 + 1

Reorder the terms:
1 + 3m + -1m = -7 + 3m + -1 + 1

Combine like terms: 3m + -1m = 2m
1 + 2m = -7 + 3m + -1 + 1

Reorder the terms:
1 + 2m = -7 + -1 + 1 + 3m

Combine like terms: -7 + -1 = -8
1 + 2m = -8 + 1 + 3m

Combine like terms: -8 + 1 = -7
1 + 2m = -7 + 3m

Solving
1 + 2m = -7 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
1 + 2m + -3m = -7 + 3m + -3m

Combine like terms: 2m + -3m = -1m
1 + -1m = -7 + 3m + -3m

Combine like terms: 3m + -3m = 0
1 + -1m = -7 + 0
1 + -1m = -7

Add '-1' to each side of the equation.
1 + -1 + -1m = -7 + -1

Combine like terms: 1 + -1 = 0
0 + -1m = -7 + -1
-1m = -7 + -1

Combine like terms: -7 + -1 = -8
-1m = -8

Divide each side by '-1'.
m = 8

Simplifying
m = 8

See similar equations:

| 21(m-994)+484=316 | | 42(x-3)=5x | | 9(u-9)=4u-31 | | 10m+5n-6m+15n= | | z+10=2 | | 7+4+8+6+2+1+6+8+9+n=60 | | -2=7(t+2)+3(2t-1) | | 4u-33=-3(u-3) | | 6+4x+3x= | | 2(y-5)+3(y+2)= | | -(4y-8)-(-3y-3)=-3 | | x+10+3x=26 | | 6x-6+7x+1=55 | | 20+16k=6 | | (46-44)+(14-21)= | | 3x+27x-9=6(5x+5) | | 128=-6n-8(-1+3n) | | 5+-3n=10 | | 12x^3-48x^2+36x=-1 | | 8+2x+7= | | 2000=25t | | 8+6(-x+7)=39+5x | | 7+2x+7x= | | 7(m-92)=-21 | | 2y+-1=-9 | | -3(2r+5)-12r+(-12)= | | 3x^4-16x^3+18x^2+x-2=0 | | y=7mx-2b | | 6x+3x+4= | | -0.5r=-6 | | 2s+3t=19 | | 8timesz=50.00 |

Equations solver categories